Editorial - Realpe Gaviria, Andrea Lorena
The impact of the Covid-19 pandemic seriously threatens working conditions, current and future employment opportunities, as well as access to technical and vocational training, jeopardizing the livelihoods and well-being of millions of people. Data published by the United Nations (UN) in 2021 showed that nearly 8 million students around the world had no connection to the Internet and no computers to continue their education.or computers to provide continuity to the formative processes at home during quarantine or alternation processes.However, the National Learning Service (SENA), one of the most beloved training entities by Colombians, has carried out deep transformation processes in order to reach all corners of Colombia with its training programs and even provide support to the Ministry of Health for the training of human talent in the vaccination processes against covid-19.Likewise, SENA through its Tecnoparques and Tecnoacademias throughout Colombia have joined in the production of biomedical equipment that was delivered to the medical personnel of institutions that required it.This has demonstrated SENA's capacity for technological development and its resilience in training processes.As part of this resilience and following SENA's mission to invest in the social and technical development of Colombian workers, the Research, Technological Development and Research System (SENNOVA), a SENA program whose purpose is to strengthen the standards of quality and relevance, in the areas of research, technological development and innovation, of the professional training provided, presents this new edition of the IDEA Construction and Wood magazine, as a tool for academic dissemination and knowledge management.This compendium of articles reflects the results of different research being carried out at the Center for Construction and Wood Technologies of SENA, on issues of sustainable construction, geomatics, construction with wood, prototyping of modular furniture, building information modeling (BIM), among other topics of interest that provide a contribution to the orange economy, the digital transformation, the industrial revolution 4.0 of the engineering, architecture, wood, infrastructure and construction sector.On this occasion we give special thanks to all those who contributed to the creation of this new edition of the IDEA Construction and Wood magazine, we invite the entire SENA community, the productive sector, academia and society in general to learn about the valuable efforts that the SENA has been making in research projects in the areas of construction and construction.We invite the entire SENA community, the productive sector, academia and society in general to learn about the valuable efforts being made by SENA in Applied Research, Technological Development and Innovation (R+D+i) projects as a contribution to the social and productive development of the country.